2008
DOI: 10.1111/j.1600-0609.2008.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Early impairment of myocardial function in young patients with β‐thalassemia major

Abstract: Study underlines that, even in a population of young, asymptomatic and well-chelated patients with TM, there is an impairment of myocardial function and that this condition could be easily detected by more advanced ultrasound techniques such as TDI and SI. The better indices of myocardial function in patients treated with deferiprone clearly needs confirmation from larger prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
(45 reference statements)
6
39
1
Order By: Relevance
“…Although some of these studies have demonstrated a significant correlation (25)(26)(27), others have not (11,28). The main limitation of TDI parameters is their dependence on heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these studies have demonstrated a significant correlation (25)(26)(27), others have not (11,28). The main limitation of TDI parameters is their dependence on heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…12 Tissue Doppler imaging (TDI) analysis disclosed, in these patients, an early myocardial dysfunction likely to be related specifically to this initial iron overload, as suggested by the correlation with cardiac T2* values. 13 In our study we could not evaluate patients by cardiac MRI or TDI, which becomes the main limitation of this study.…”
Section: Discussionmentioning
confidence: 91%
“…In literature, we found few studies conducted in beta thalassemia patients which can be compared with our study (18)(19)(20)(21)(22). Specifically, tissue Doppler examination in the study performed by Vogel et al (18) included segmentary measurements as in our study.…”
Section: In 2001mentioning
confidence: 81%
“…When conventional findings of heart failure are observed on echocardiography, the prognosis of cardiomyopathy is frequently fatal (17). Recently, introduction of tissue Doppler for evaluation of diastolic function indicates that significant advances will be made in terms of early diagnosis of cardiomyopathy in patients with thalassemia major (18)(19)(20)(21)(22). In additon, usage of T2-star imaging method showing cardiac iron load has been the most important development for early diagnosis of risk of heart-related complications in recent years (23).…”
Section: Discussionmentioning
confidence: 99%